Improving Electrical Properties in Lead-Free BNT Based Ceramics by BLT Doping. Issue 1 (29th December 2021) - Thongmee, Navavan; Sumang, Rattiphorn
Abstract: (1- x )Bi0.5 Na0.5 TiO3 - x (Bi3.25 La0.75 )Ti3 O12 ; (1- x )BNT- x BLT ceramics with x = 0–0.20 wt.% were prepared by solid-state reaction method. The Bi0.5 Na0.5 TiO3 (BNT) and (Bi3.25 La0.75 )Ti3 O12 (BLT) powders were calcined separately. The BNT powder was calcined at 850 °C for 2 h. and BLT powder at 750 °C for 4 h. The (1- x )BNT- x BLT samples were sintered between 1050 °C and 1200 °C for 4 h. All samples exhibit almost a pure perovskite phase with coexistence of rhombohedral and orthorhombic phases. The average grain size decreased with increased in x (BLT) contents. The maximum density and relative density of about 5.87 ± 0.11 g/cm 3 and 97.2% were obtained for the composition of 0.97BNT–0.03BLT. The temperature at maximum permittivity ( T m ) tended to increase from 324 °C to 341 °C with increase in x (BLT) contents. The results revealed that the fatigue behavior was improved in the sample of 0.97BNT–0.03BLT, where a slight decrease in remanent polarization with low degradation of ferroelectric properties was observed after electrical fatigue.